Unfolded protein response IRE1/XBP1 signaling is required for healthy mammalian brain aging - Cabral‐Miranda, Felipe; Tamburini, Giovanni; Martinez, Gabriela; Ardiles, Alvaro O; Medinas, Danilo B; Gerakis, Yannis; Hung, Mei‐Li Diaz; Vidal, René; Fuentealba, Matias; Miedema, Tim; Duran‐Aniotz, Claudia; Diaz, Javier; et al. (The EMBO journal, 2022)
Aging is a major risk factor to develop neurodegenerative diseases and is associated with decreased buffering capacity of the proteostasis network. We investigated the significance of the unfolded protein response (UPR), a major signaling pathway activated to cope with endoplasmic reticulum (ER) stress, in the functional deterioration of the mammalian brain during aging. We report that genetic disruption of the ER stress sensor IRE1 accelerated age‐related cognitive decline. In mouse models, overexpressing an active form of the UPR transcription factor XBP1 restored synaptic and cognitive function, in addition to reducing cell senescence. Proteomic profiling of hippocampal tissue showed that XBP1 expression significantly restore changes associated with aging, including factors involved in synaptic function and pathways linked to neurodegenerative diseases. The genes modified by XBP1 in the aged hippocampus where also altered. Collectively, our results demonstrate that strategies to manipulate the UPR in mammals may help sustain healthy brain aging. Synopsis The UPR pathway sustains brain function, delaying the natural appearance of age‐associated phenotypes in mammals. IRE1/XBP1 signaling improves neuronal physiology, possibly by regulation of synaptic protein expression. Impairment of UPR signaling begins by middle age in the mouse brain. Ablation of IRE1 expression in the brain accelerates and exacerbates age‐associated cognitive decline. Overexpression of XBP1s, the active form of XBP1, in the brain improves age‐associated phenotypes in mice. XBP1s gene delivery to aged mice can revert brain dysfunction at the morphological, electrophysiological, molecular, and behavioral level. Proteomic profiling of aged animals overexpressing XBP1s highlights the modification of pathways related to synapse physiology and neurodegeneration. Graphical Abstract The unfolded protein response signaling components IRE1 and XBP1 are shown to play a role in age‐associated cognitive function and brain health in mice.